Molecular Assembly of Ground-State Cooled Single Atoms - L. R. Liu (American Physical Society, 2019)
We demonstrate full quantum state control of two species of single atoms using optical tweezers and assemble the atoms into a molecule. Our demonstration includes 3D ground-state cooling of a single atom (Cs) in an optical tweezer, transport by several microns with minimal heating, and merging with a single Na atom. Subsequently, both atoms occupy the simultaneous motional ground state with 61(4)% probability. This realizes a sample of exactly two cotrapped atoms near the phase-space-density limit of one, and allows for efficient stimulated-Raman transfer of a pair of atoms into a molecular bound state of the triplet electronic ground potential a^{3}Σ^{+}. The results are key steps toward coherent creation of single ultracold molecules for future exploration of quantum simulation and quantum information processing.